Perancangan Aplikasi Simpan Pinjam dengan Gamifikasi untuk Peningkataan Partisipasi Anggota Koperasi Simpan Pinjam - Ilham Adi Maulana; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
Savings and loan cooperatives are financial institutions owned and operated by their members to provide savings and loan services for their economic welfare. This research aims to design a web-based application with a gamification model at the Usaha Mandiri Savings and Loans Cooperative. This model is expected to increase member involvement and cooperative growth through technological innovation. It is hoped that the application of this gamification will maintain the relevance of cooperatives in the digital era, as well as encourage members' active participation in cooperative activities. This research not only provides insight into the application of gamification in a cooperative context but also practical guidance for application developers to increase member participation and organizational growth. In addition, this research serves as inspiration for the development of technology and innovation in the cooperative sector. With this gamification model, cooperatives are expected to be able to adapt to the challenges of the digital era and continue to provide greater benefits for their members and the wider community.